O sair do papel: uma avaliação da formulação e implementação do II Plano Estadual para Erradicação do Trabalho Escravo no Maranhão - COELHO , Dayana Carvalho (2020)
Evaluation of the formulation and implementation of the II State Plan for the Eradication of Slave Labor in Maranhão (II Pete-MA). It assesses the effectiveness and efficiency (technical and social) of the II Pete-MA, identifying the advances and barriers generated during its execution. It concepts and contextualizes contemporary slavery and the process of constructing policies to fight slave labor in Brazil and Maranhão. The political and institutional cooperation or matrixes conflicts that permeate the formulation and implementation of these policies at the national and state levels are explicit, differentiating strategic subjects, interest groups, partners and support networks, discussing how they relate and articulate to define their execution. As an evaluative research, it uses specific procedures to social research, guided by a critical dialectical perspective, supported by the Marxian categories of history, contradiction and totality. Methodologically, it uses literature review, bibliographic survey, analysis of documents and data on the formulation and implementation of the II Pete-MA, complemented with semi structured interviews and systematic observation of the forums and the process of construction and execution of the evaluated policy. It identifies and evaluates the II Pete-MA's implementation strategy, based on its component systems and processes, analyzing the extent to which they achieved the planned goals and satisfied implementers and beneficiaries. It discusses the advances and barriers resulting from the implementation of II Pete-MA, recommending changes to achieve greater effectiveness and efficiency with the local implementation of policies to combat contemporary slavery. It seeks to contribute to the quantitative and qualitative survey of information that enables decision making by managers and social control over the actions developed in Maranhão to eradicate slave labor.